GAMBARAN PERKEMBANGAN PUBERTAS DAN PERBEDAAN USIA AWAL PUBERTAS PADA SISWA - SISWI SEKOLAH DASAR (Studi di Kecamatan Semarang Tengah Kota Semarang) - Milka Noviananda Hardy; Lintang Dian Saraswati; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Puberty is a development process from childhood to adulthood with physical and physiological changesleading to sexual maturity and reproductive capacity. Improving nutrition is assumed to be responsible for secular trend to earlier onset of puberty and sexual maturity in develop and development countries. Early onset of puberty are known as the risk factor for breast cancer, prostate cancer, obesity and mental disorder. The aim of this research was to describe the difference of pubertal timing between boys and girls in elementary students in Central Semarang and to describe some factor associated with early onset of puberty and early sexual maturity. This research was a comparative study that use cross sectional design with descriptive survey. The population of this study were all boys in grade IV,V,VI and girls grade III,IV,V,VI. 126 boys and 166 girls were choosen by using proportionate statified random sampling method. The result showed that prepubertal stage was mostly found in boys (55,6%) than in girls (45,2%).Mean age of pubertal onset in boys is ±10,9 year and in girls in ±10 years. The onset of puberty in boys and girls were found earlier than current standard, but girls begin their puberty faster than boys. Parents should pay more attention to children’s dietary and education about puberty. Children also need to get more education about puberty in school.